منهج الإمام مالك في الفتوى وتأثر علماء الغرب الإسلامي بمنهجه - الرشيدد.مبروكة محمد علي (Aljameai, 2022)
الملخص: يعد المذهب المالكي من المذاهب الإسلامية التي لقت إقبالا واسعا في الغرب الإسلامي، ولصاحبها فضل كبير في تأصيل الأصول المعتمدة في الفقه الإسلامي، وتقرير الفروع المبنية عليها، وقد كان الإمام مالك ممن أعتنى بالفتوى تصنيفًا وتأليفا، ويعد ممن فتح الباب لمن جاء بعده من علماء المغرب الإسلامي من تلاميذه للعمل بالفتوى، التي انطلقت في الغرب الإسلامي بدخول المذهب المالكي فيه. بناء على ذلك قامت الباحثة بالكتابة في منهج الإمام مالك، ومن تأثر به ووسمت البحث بـــــ(منهج الإمام مالك في الفتوى و تأثر علماء الغرب الإسلامي بمنهجه) وقد أخذت الإمام المازني و الشاطبي كنماذج لدراسة منهجهم، واقتصرت على هؤلاء؛ لكثرت علماء المالكية مما يشكل صعوبة في حصرهم في مثل هذا البحث، ويتطلب دراستهم في رسائل ماجستير ودكتوراه ولن يستطاع حصرهم. Abstract: The Maliki doctrine of thought is one of the Islamic doctrines of thought that has gained wide popularity in the Islamic West, Its owner has great merit in rooting the principles adopted in Islamic jurisprudence, and deciding of the branches on which it is based, Imam Malik was one of those who took care of the fatwa, compilation and compilation, He is considered one of those who opened the door for those who came after him from among the scholars of the Islamic West to work with fatwa, Which started in the Islamic West with the entry of the Maliki doctrine of thought in it. Accordingly, the researcher wrote in the approach And whoever was affected by it, he gave him the following address: by (The approach of Imam Malik in the fatwa and the scholars of the Islamic West influenced by his approach)